2011
DOI: 10.1111/j.1467-9566.2011.01320.x
|View full text |Cite
|
Sign up to set email alerts
|

The pharmaceuticalisation of society? A framework for analysis

Abstract: Drawing on insights from both medical sociology and science and technology studies this article provides a critical analysis of the nature and status of pharmaceuticalisation in terms of the following key dimensions and dynamics: (i) the redefinition or reconfiguration of health 'problems' as having a pharmaceutical solution; (ii) changing forms of governance; (iii) mediation; (iv) the creation of new techno-social identities and the mobilisation of patient or consumer groups around drugs; (v) the use of drugs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
211
0
53

Year Published

2014
2014
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 301 publications
(266 citation statements)
references
References 54 publications
(70 reference statements)
2
211
0
53
Order By: Relevance
“…She acknowledges the role of physician and patient expectations in the use of these medicines but suggests that the pharmaceutical companies' control over the organisation and funding of research and its ability to shape the information landscape is a key factor. On this basis she argues that pharmaceuticalization should not just be restricted to cases involving a re-designation of a condition as suitable for pharmaceutical intervention with a new or existing drug, as implied in the literature (Abraham 2009, Williams et al 2011a. Rather it should encompass any instance of medicines expansion in use, including the increasing application of existing drugs to meet the established need of an existing patient population.…”
Section: Markets For Medicinesmentioning
confidence: 99%
See 2 more Smart Citations
“…She acknowledges the role of physician and patient expectations in the use of these medicines but suggests that the pharmaceutical companies' control over the organisation and funding of research and its ability to shape the information landscape is a key factor. On this basis she argues that pharmaceuticalization should not just be restricted to cases involving a re-designation of a condition as suitable for pharmaceutical intervention with a new or existing drug, as implied in the literature (Abraham 2009, Williams et al 2011a. Rather it should encompass any instance of medicines expansion in use, including the increasing application of existing drugs to meet the established need of an existing patient population.…”
Section: Markets For Medicinesmentioning
confidence: 99%
“…Which sources are used depends on how individual students think and feel about their non-medical drug usage. On this basis it is argued that prescription stimulant diversion is characterised by a significant degree of complexity and heterogeneity, a key point made by Williams et al (2011a) in their discussion of pharmaceuticalization. This is important in pointing to limits in the extent of non-medical enhancement use.…”
Section: From Treatment To Enhancement -The Use Of Drugs For Non-medimentioning
confidence: 99%
See 1 more Smart Citation
“…Note that on this list, in addition to prevention and treatment of possible disease, we find an opportunity to improve conditions that, in principle, can be considered as part of the normal course of life but that have been medicalized, as many studies have shown (Rosenberg, 2002;Martin, 2006;Conrad, 2007;Rose, 2007;Clarke et al, 2010;Dumit, 2012;Marshall, 2010;Williams et al, 2011).…”
Section: That Loving Feeling Is Now For Salementioning
confidence: 99%
“…Though lay activism and consumerism are described as playing a part in the expansion of pharmaceutical use (Abraham 2010b, Bell and Figert 2012, Williams, Martin and Gabe 2011, there is more to do to understand pharmaceutical consumers and consumerism.…”
mentioning
confidence: 99%